Queer stepfamilies : the path to social and legal recognition - Acosta, Katie L., 1980- (New York University Press, 2021)
"Lesbian, bisexual, and queer families formed after the dissolution of a marriage face a range of obstacles. In Queer Stepfamilies, Katie L. Acosta offers a wealth of insight into their complex experiences as they negotiate parenting among multiple parents and family-building in a world not designed to meet their needs. Drawing on in-depth interviews, Acosta follows the journeys of more than forty families as they navigate a legal and social landscape that fails to recognize their existence. Acosta contextualizes the legal realities of LGBTQ stepparent families and considers the actions these parents take to protect their families in the absence of comprehensive policies or laws geared to meet their needs. Queer Stepfamilies reveals the obstacles these families face in family courts during divorce proceedings and custody cases, and highlights their distrust of courts when it comes to acting in their children's best interests, especially in the event of an origin parent's death. As LGBTQ families continue to make social and legal strides in acceptance and recognition, this important book shows how queer stepparents find ways to make their unconventional families work, despite the many social and legal obstacles they encounter. Acosta provides a fresh perspective, broadening our understanding about families in the twenty-first century"--